The breast cancer patient in the cardioncology unit - Cardinale, Daniela; Caruso, Vincenzo; Cipolla, Carlo M. (Journal of Thoracic Disease, 2018)
The breakthroughs of breast cancer management have led to a significant improvement in patient survival. However, to obtain this outcome a considerable price has been paid regarding cardiovascular side effects. Indeed, cardiovascular disease is the main cause of mortality in patients with breast cancer over fifty years of age, contributing more than cancer mortality in older cancer survivors. Thus, the identification and the management of patients with breast cancer at risk for cardiovascular events has become critical in order to reduce morbidity and mortality from cardiovascular toxicity due to cancer therapy, which may blunt its effectiveness. Today, cardioncology is a novel and recognized medical discipline, which aims to encourage a close interaction between cardiology and oncology, explore new strategies, collect evidence-based indications, and develop interdisciplinary expertise with the ultimate goal of minimize the risk of developing cardiovascular disease during and after anticancer therapy, prevent the breast cancer patient cured today from becoming the heart patient of tomorrow, and avoiding the possibility that pre-existent cardiac disease be a barrier leading to a reduction of a patient’s therapeutic opportunities. In this review we discussed the advantages of a cardioncology approach in terms of risk stratification, monitoring for early diagnosis, prevention, and early treatment of cardiotoxicity.